Refining the Rib-sparing Approach in Microsurgical Breast Reconstruction: Keys to Success - Hamilton, Kristy; Zavlin, Dmitry; Doval, Andres F.; Spiegel, Aldona J. (Journal of Reconstructive Microsurgery, 2021)
Background Free tissue transfer using microsurgical techniques is a popular option for breast reconstruction, and the internal mammary vessels remain the most popular recipient vessels for the anastomosis. Traditionally, ribs were resected for better access to these vessels in the intercostal space. However, rib resection has the potential for complications and adds a surgical step. Here, the authors evaluate and compare both techniques in a retrospective study as well as offer technical pearls.Methods The 400 most recent consecutive patients who underwent microsurgical breast reconstruction by a single surgeon were retrospectively reviewed. 54 patients underwent the traditional rib-resecting approach. 346 patients underwent the rib-sparing approach, which was the preferred approach of the senior author, when possible. Patients requiring the rib-resecting approach were distributed evenly throughout the series. Primary outcomes were any immediate post-operative complications.Results Between the two clinical groups, there was no difference between demographic or clinical details, the flap type, history of previous radiation, or timing of reconstruction. Complications of any kind as well as the subset of complications were significantly more frequent in the rib resection than in the rib-sparing group. Specifically, the rate of reanastomosis was higher in the rib resection group [10.6 vs 2.7%, p < 0.001] as was the frequency of return to the OR in the immediate post-operative setting [3.0 vs 0.3%, p < 0.001]. There is a 4.50 odds ratio of having a complication in a rib resection case versus rib sparing [CI: 1.97–10.30, p < 0.001]. All cases were initiated with the intent to perform a rib-sparing approach if possible, and they were converted to a rib-resection approach as needed.Conclusion In the largest reported series to date, the rib-sparing approach is demonstrated to be both safe and efficacious in microsurgical breast reconstruction.
Keywords: breast reconstruction; DIEP flap; rib resection; rib sparing; anastomosis; outcomes